RELATIONSHIP OF SEDIMENTATION RATE WITH SEAGRASS COMMUNITY STRUCTURE AND ORGANIC CARBON STOCK IN THE SEAGRASS ECOSYSTEM OF INNER AMBON BAY - Niclas Tulalessy, Stenly
Sediment disturbance is an environmental problem which may harmful to the coastal ecosystems. Sedimentation that has occurred in the inner Ambon bay can damage both seagrass ecosystems and communities not to mention affecting the role of seagrass ecosystems as organic carbon storage. This study aims to; (1) examine the rate of sedimentation in the TAD coastline; (2) examine the organic carbon deposits in seagrass ecosystems in TAD; (3) Analyzing the relationship between sedimentation rate and the community structure; and 4) Analyzing the relationship between sedimentation rates and organic carbon deposits in TAD. The study began with an analysis of vegetation at four seagrass ecosystem stations on TAD coast. Subsequently, researcher conducted sampling from sediments and seagrass plants that had been collected. The organic carbon contents were measured from the obtained samples using the Walkley and Black methods. Meanwhile, sedimentation rates were measured at all four research stations using sediment traps. Besides, by utilizing the leaf-marked and root biomass methods, researcher also measured carbon sequestration of seagrass. The data obtained were then analyzed statistically. The results revealed that there were 5 species of seagrass in the four research stations in TAD namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halophyla minor, and Halodule pinifolia. The finding expossed that carbon stock in seagrass ranged from 0.53 to 0.91 Mg C ha-1 while in sediments were about 5.56-10.51 Mg C ha-1. The measured sedimentation rate in the Ambon seagrass ecosystem using a sediment trap was 0.19-0.44 Kg m-2 days-1. Pearson correlation analysis results showed a strong significant positive relationship between the densities of seagrass Enhalus acoroides with the sedimentation rate (R=0,723). However, the sedimentation rate has no relationship with the density of T. hemprichii (R=-0,079). Sedimentation that occurred also negatively affected the diversity of seagrasses in the inner bay of Ambon which was found that, stations with high sedimentation rates had a low diversity index. The sedimentation did not have a significant effect but tend to be negative to the stock of organic carbon of sediment in the inner Ambon bay (R=0,266). The research also found that the source of organic carbon of seagrass sediment is more autochthonous because it is generally dominated by large seagrass. The carbon sequestration measurements found that E. acoroides has a higher sequestration ability (2,56 g C m-2 day-1) compare to T. hemprichii (1,06 g C m-2day-1). In addition, the root organ and rhizome have the largest carbon storage compared to the parts of the shoot.